2022
DOI: 10.3390/app12199912
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biodiesel by Interesterification of Triglycerides with Methyl Formate

Abstract: In the conventional synthesis of biodiesel, not only fatty acid esters (biodiesel) are formed, but also the by-product is the glycerol phase, which amounts to about 10 wt.%. Recently, the studies on the interesterification of oil using carboxylate esters have been launched. In this case, no glycerol is formed, and esters of glycerol and short-chain organic acids soluble in biodiesel are produced. The biodiesel yield is increased, and the biodiesel production process is more economically viable. The process of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
0
0
Order By: Relevance
“…However, at a higher MA:O ratio, the additional catalyst can effectively utilize the abundant methyl acetate for efficient biodiesel production. References supporting this interaction effect include Sendzikiene et al [31], where the optimal catalyst loading was found to be dependent on the reactant ratio used in biodiesel production via interesterification. These findings highlight the importance of using response surface methodology (RSM) to optimize the interesterification process for biodiesel production.…”
Section: Effect Of Process Parametersmentioning
confidence: 92%
See 1 more Smart Citation
“…However, at a higher MA:O ratio, the additional catalyst can effectively utilize the abundant methyl acetate for efficient biodiesel production. References supporting this interaction effect include Sendzikiene et al [31], where the optimal catalyst loading was found to be dependent on the reactant ratio used in biodiesel production via interesterification. These findings highlight the importance of using response surface methodology (RSM) to optimize the interesterification process for biodiesel production.…”
Section: Effect Of Process Parametersmentioning
confidence: 92%
“…The independent variables for the catalytic interesterification of WCO with methyl acetate and sulfuric acid were selected based on a review of the literature and the reactant characteristics [31]. The experimental design included three independent variables: reaction time (coded as A), methyl acetate to oil molar ratio (coded as B), and sulfuric acid concentration (coded as C), as shown in Table 1.…”
Section: Experimental Designmentioning
confidence: 99%
“…Although some of the glycerol is removed by sedimentation, the remaining glycerol phase is estimated at 10% [63]. Triglycerides are the fatty acids of glycerol, the main constituents of lipids, mostly represented by vegetable oils from which BFA is obtained [30,64]. For this reason, they are found in higher amounts in rapeseed oil and BRO.…”
Section: Statistical Processing Of the Quality Parameters Of Bro And Bfamentioning
confidence: 99%